Gross Negligence (Medical) Manslaughter and the Puzzling Implications of Negligent Ignorance: Rose v R [2017] EWCA Crim 1168. (22nd May 2018) - Mullock, Alexandra
ABSTRACT: This commentary explores the Court of Appeal's decision in the case of Rose 1 in order to assess the risk of liability for gross negligence manslaughter currently faced by the medical profession in the event that negligence causes the death of a patient. Subtly modifying the test established in Adomako, 2 Rose confirms that in order to be potentially liable, there must be a serious risk of death that was, rather than ought to have been, obvious/foreseeable to the defendant. Consequently, in more complex cases where the serious risk of death is not immediately obvious, negligently failing to assess risk seems to prevent potential liability on the basis that the putative defendant was in a position of negligent ignorance.